Verifikasi Hukum Boyle dan Tekanan Hidrostatik Dengan Barometer Digital PS-3203 - Sumampouw, Jelovendra; Pilat, Geraldy; Lumembang, Megastin Massang; Kolibu, Hesky Stevy (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2026)
This study investigates the relationship between gas pressure–volume behavior and liquid pressure–depth characteristics through experiments utilizing a PS-3203 pressure sensor. The objective is to quantitatively verify Boyle’s Law for gases and the hydrostatic pressure principle for liquids using digital pressure measurements. In the gas experiment, the air volume was adjusted using a syringe, and the pressure was recorded automatically. The results demonstrate an inverse proportionality between pressure and volume, confirming the equation . In the liquid experiment, pressure was observed to increase linearly with depth, with a gradient of 0,096 kPa/cm, corresponding to a water density of 979,6 kg/m³, indicating an approximate 2% deviation from the theoretical value. These findings validate both physical laws and demonstrate that the PS-3203 digital sensor can accurately verify Boyle’s Law and hydrostatic pressure while improving measurement precision and experimental efficiency.